Effect of vacuum aging and influence of sire on palatability of beef longissimus from grass-FED F1 senepol x zebu bulls - Huerta Leidenz, Nelson; Rodas González, Argenis; Smith, Gary (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; span.ft12 mso-style-name:ft12; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Fourteen carcasses from grass-fed F1 Senepol crossbred bulls (from 3 Senepol bulls mated to 14 Nellore -influenced cows) were electrically stimulated, and longissimus muscle samples were aged for three periods (2, 7 or 14 d) to study cooking traits, Warner-Bratzler shear force (WBS) values and sensory panel ratings for palatability attributes. Sire affected (P=0.001) WBS values. As compared to control (2 -d aged) steaks, those steaks aged 7 or 14 d cooked slower (P < 0.05), had lower WBS values (P < 0.05), and rated as more tender (P < 0.01), with lesser amounts of connective tissue (P < 0.01), and more intense in flavor (P < 0.01). In the control group, 42.9% of the steaks were classified as Tender (WBS<3.88 kg), 21.4% Intermediate (WBS= 3.88 to 4.98 kg) and 35.7% Tough (WBS>4.98 kg). By d 14, 71.4% of the steaks were Tender, 21.4% Intermediate and 7.1% Tough. Aging of steaks from these grass -fed bulls reduced the proportion of tough steaks from 35.7% (d 2, control) to 21.4% (d 7) and 7.1% (d 14).